ANTIOXIDANT ACTIVITY OF VARIOUS EXTRACTS OF JARAK TINTIR (Jatropha multifida L.) STEM, PHENOLIC AND FLAVONOID CONTENT - Syam, Akhirul Kahfi; Windyaswari, Ari Sri; Ratnawati, Julia (Universitas Bhakti Kencana, 2020)
Background: Jarak tintir (Jatropha multifida L.) was identified as one of family Euphorbiaceae and used by Indonesian people as traditional medicine. This study aimed to measure IC50 of inhibition DPPH as free radicals and make statistical analysis of flavonoid and phenolic content and correlation with their IC50 of free radicals. Methods: Hot continuous extraction was done with Soxhlet apparatus using various polarity solvents (n-hexane, ethyl acetate, and methanol). Results: Methanol extract had the lowest IC50 32.26 ± 0.37 µg/mL of DPPH inhibition activity. Ethyl acetate extract had highest phenolic and highest flavonoid content with 35.21 ± 1.50 mg TAE/g extract and 49.41 ± 1.65 mg QE/g extract. Conclusion: Flavonoid and phenolic content in extracts had linier correlation with their IC50 of inhibition free radicals.